Dysregulation of PLDN (Pallidin) is a mechanism for platelet dense granule deficiency in RUNX1 haplodeficiency - Mao, G.F. (J Thromb Haemost, 2017)
BACKGROUND: Inherited RUNX1 haplodeficiency is associated with thrombocytopenia and platelet dysfunction. Dense granule (DG) deficiency is reported in patients with RUNX1 haplodeficiency, but the molecular mechanisms are unknown. Platelet mRNA expression profiling in a patient previously reported by us with a RUNX1 mutation and platelet dysfunction showed decreased expression of PLDN (BLOC1S6), which encodes for pallidin, a subunit of BLOC-1 (biogenesis of lysosome-related organelles complex-1) involved in granule biogenesis. PLDN mutations in the pallid mouse and the Hermansky-Pudlak syndrome (HPS)-9 are associated with platelet DG deficiency. OBJECTIVES: We postulated that PLDN is a RUNX1 target and that its decreased expression leads to platelet DG deficiency in RUNX1 haplodeficiency. RESULTS: Platelet pallidin and DG were decreased in our patient. This was also observed in two siblings from a different family with a RUNX1 mutation. Chromatin immunoprecipitation and electrophoretic mobility shift assays using phorbol ester-treated human erythroleukemia (HEL) cells showed RUNX1 binding to RUNX1 consensus sites in the PLDN1 5′ upstream region. In luciferase reporter studies, mutation of RUNX1 sites in the PLDN promoter reduced activity. RUNX1 over-expression enhanced and RUNX1 downregulation decreased PLDN1 promoter activity and protein expression. RUNX1 downregulation resulted in impaired handling of mepacrine and mislocalization of DG marker CD63 in HEL cells, indicating impaired DG formation, with recapitulation of findings on PLDN downregulation. CONCLUSIONS: These studies provide the first evidence that PLDN is a direct target of RUNX1 and its dysregulation is a mechanism for platelet DG deficiency associated with RUNX1 haplodeficiency.